Folk Uses of some Medicinal Plants of Dobhan VDC of Palpa District, Western Nepal - Gautam1; D.D.Tewari2, Anant Gopal Singh1*, Laxman Prasad (Journal of Phytology, 2011)
The study has made an effort in order to explore and document indigenous knowledge and practice of Magar community of Dobhan VDC of Palpa district of western Nepal. Three study visits over a period of nine months from August 2010 to April 2011in the study area were made to collect primary information on the medicinal plants by field observation, transect work, interviews, focus group discussions, case study etc. Altogether 48 medicinal plants were recorded which are used to cure various human diseases like skin diseases, sinusitis, fever, toothache, eye infection, rheumatic pain, chest pain, backache, colic pain urinary problem, stomach troubles, gastric, fever, cold and cough, headache, liver disorders etc. For the treatment of different health problems, people of the study area come to Dhami, Jhankari, Guruwa, ojha from local level outside VDC, National and International level too. Especially elderly people and healers have knowledge about the medicinal plants and their uses in health care. With their long experiences and practices, they have acquired rich knowledge about the utilization of plant resources in various ways. It is found that medicinal plants are the first levels of health care providers to majority of the people in the study area. Medicinal plants of this area are highly threatened due to various human related activities like deforestation, habit destruction, unsustainable harvesting of forest products etc. Besides, due to various ecological, social and economic factors, the indigenous knowledge of the people is under great threat. Therefore, for the conservation and preservation of indigenous knowledge on medicinal plants, some recommendations have also been made based on the present study.